Knowledge, Attitude, and Practice Related to Diabetes with Reference to Ayurveda and Yoga: An Institutional Survey - Vrinda; Sulochana, Bhat; Anagha, Jenu; Kavya, N; Monica, K P (International Research Journal of Ayurveda & Yoga, 2025)
Background: Diabetes mellitus has become a common disease among Indian population, with the rate of incidence of pre-diabetes increasing gradually. Their conversion to diabetes is rapid among Indians. This scenario is mainly due to unawareness of the condition. Hence, this study aims to evaluate the knowledge, attitude, and practice (KAP) related to diabetes in conjunction with the use of Ayurveda and Yoga for the same among visitors of Central Ayurveda Research Institute, Bengaluru. Materials and Methods: An institutional-based, cross-sectional survey study was conducted with a sample size of 350 from October 2022 to January 2023. The data collected were analyzed statistically with a confidence interval of 95% and 5% error. Multivariate analysis with three separate ordinal logistic regressions was performed for KAP, keeping the background characteristics of the individual as independent variables. Results: About 67.14%, 42.29%, and 74.57% had excellent knowledge, positive attitude, and good practice, respectively. Increase in age, female respondents, and mental stress had a significant association with knowledge. Rural residents and diabetic patients carried a positive attitude towards diabetes. Higher age was the only determinant of practice. Conclusion: This study infers a satisfactory prevalence of knowledge and practice related to diabetes. However, there is a lack of a positive attitude. Proper education to refute the myths and strategies to provide appropriate guidance to make use of Ayurveda and Yoga for diabetes must be promoted.